Zebrafish (Danio rerio) model as an early stage screening tool to study the biodistribution and toxicity profile of doxorubicin-loaded mixed micelles - Calienni, Maria Natalia (2018)
Doxorubicin (DOX) hydrochloride is a powerful anthracycline antibiotic used for the treatment of various types of malignancies, particularly ovarian and metastatic breast cancer. However, DOX presents severe side effects, such as hepatotoxicity, nephrotoxicity, dose-limiting myelosuppression, brain damage and cardiotoxicity. A liposomal formulation, Doxil® was approved by the FDA, which has managed to reduce the number of cardiac events in patients with metastatic breast cancer. However, in comparison to free DOX, Doxil® has not shown significant improvements regarding survival. We have previously designed DOX-loaded mixed micelles (MMDOX) composed of D-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) and Tetronic® T1107. To assess the potential toxic effects of this novel formulation, in this work the zebrafish (Danio rerio) model was used to evaluate its in vivo toxicity and teratogenicity. This study evaluated and compared the effects of DOX exposure from different formulations (free DOX, MMDOX and Doxil®) on the swimming activity, morphological alterations, cardiac rhythm, lethality rate and DOX biodistribution. MMDOX showed lower lethal effects, morphological alterations and neurotoxic effects than the free drug. This study shows the potential of the MMDOX to be an effective DOX-delivery system because it could reduce the side effects.